Regioselectivities of Nitration of Toluene on Bentonite Catalysts by the Use of Alkyl Nitrates - Wen, N.; Peng, X.; Xu, W. (Asian Journal of Chemistry, 2012)
Regioselectivities of nitration of toluene were investigated on the acid-treated bentonites catalysts by using alkyl nitrates. The reaction was highly para selective, compared as composition (ortho/para = 1.63) of nitro isomers of nitration of toluene with sulfonitric acid, up to ortho-to-para ratios of 0.52, 0.47, 0.41 and 0.41, respectively, when using n-propyl nitrate, iso-propyl nitrate, cyclohexyl nitrate, iso-octyl nitrate on bentonite of sulfuric acid treatment for 1 h. A radical cationic component was proposed to elucidate nitration mechanism according to the calculated and experimental results.